Blood cell-derived extracellular vesicles: diagnostic biomarkers and smart delivery systems. Issue 1 (1st January 2021) - Xu, Limei; Liang, Yujie; Xu, Xiao; Xia, Jiang; Wen, Caining; Zhang, Peng; Duan, Li
ABSTRACT: Extracellular vesicles (EVs) are released by most of the cells or tissues and act as nanocarriers to transfer nucleic acids, proteins, and lipids. The blood system is the most abundant source of extracellular vesicles for purification, and it has attracted considerable attention as a source of diagnostic biomarkers. Blood-derived extracellular vesicles, especially vesicles released from erythrocytes and platelets, are highly important in nanoplatform-based therapeutic interventions as potentially ideal drug delivery vehicles. We reviewed the latest research progress on the paracrine effects and biological functions of extracellular vesicles derived from erythrocytes, leukocytes, platelets, and plasma. From a clinical perspective, we summarize selected useful diagnostic biomarkers for therapeutic intervention and diagnosis. Especially, we describe and discuss the potential application of erythrocyte-derived extracellular vesicles as a new nano-delivery platform for the desired therapeutics. We suggest that blood-derived extracellular vesicles are an ideal nanoplatform for disease diagnosis and therapy.